Financial Accounting as a Driving Force to Redefine the Conception of Business - Pardo López, Steven (Editorial Pontificia Universidad Javeriana, 2018)
The prevalent practice of the business financing has prioritized a business conception whereby the shareholder, financial management and value creation emerge as elements determining the relationship between the organizational agents. The reproduction of such conception in economies lacking strong financial structures then becomes the focus of this study. In this vein, this work explores the decline of the industrial sector and the rise of the financial sector in Colombia. Additionally, this work identifies the emerging tensions between the organizational reality and the institutional environment due to the rise of the business financial conception at the expense of the business organic conception. The study concludes that theses tensions can be overcome by using an institutional isomorphism in which the international accounting upgrades will play a central role. These upgrades will bring into the organizational reality a set of techniques and rationalities related to speculative activities.